PENGARUH BEBAN KERJA PEGAWAI TERHADAP STRES KERJA DI RUANG PROGRAM DAN PEMASARAN RUMAH SAKIT UMUM DAERAH KOTA BANDUNG - Ceria Febiana; Virliana Utami (Jurnal Infokes, 2020)
This research aims to determine the effect of employee work capacity on work stress. The method used is a quantitative method using the validity test, realibility test, spearman rank correlation data analysis and the coeficient of determination test. Based on the calculation of the rank-spearman variable X ( employee work capacity ) and variable Y (work stress ) of 0,577 which is interpreted to be moderate. Based on the coefficient of determination the effect of workload on employee work stress by 33,29% and the remaining 66,71%. As for the problems contained in the program room and marketing of public hospitals in the city of Bandung, some employees often work overtime to complete their work. The advice that will be given by the author for this problem is that the workload of employees needs to be optimally pursued by the working hours that have been set.